Usage and understanding of food labels among Lebanese shoppers - Dimassi, Hani (2017)
Food labelling is a population-based approach to health education that enables consumers to make better choices by providing information at the point of purchase. This study aimed to assess the food label usage and understanding and factors affecting them among Lebanese supermarket shoppers. A cross-sectional study was conducted among 748 supermarket shoppers in Lebanon between December 2013 and February 2014 using a pre-coded structured questionnaire. About 29.3 of the shoppers check the food labels every time they buy a food product and 15.7% never do it. Shoppers who do not read food labels identified the long time needed in reading them as top reason (34.9%), while 9.8% answered that they do not understand them. About 55.4%of the surveyed shoppers read the food labels at the supermarkets. About 44.4% of participants agreed that reading food labels is very important, while 30.3% read the food labels depending on the purchased product. Then 19.4% of participants complained that food labels contain too much information and 13.8% claimed that food labels are difficult to understand. About 60.3% think that food labels have helped people in changing their eating habits, while health and nutrition claims affected the product selection among 59.8% of participants. The food label knowledge score average was 63.1%. Older, obese shoppers having kids, suffering from chronic illness or allergies, following a specific diet and residing in big cities scored significantly (p < .05) higher. The low knowledge score necessitates the nutrition education on how to read and use the food labels. Groceries would be the perfect place to reach out mass consumers.